Impact of overseeding cool-season annual forages on spring regrowth of tifton 85 bermudagrass - Reis, R. A.; Sollenberger, L. E.; Urban, D. (Fundação Estudos Agrarios Luiz Queiroz (fealq), 2001)
Field observations have shown stand reduction and slow spring regrowth of Tifton. 85 bermudagrass (Cynodon spp.) pastures overseeded with temperate forages for grazing during the cool season. This experiment compared the effect of cool-season management programs, including overseeding and use of different grazing treatments, on productivity of Tifton 85 the following warm season. There were seven treatments: four were bermudagrass overseeded with a cool-season annual forage mixture (two grasses and two legumes) and grazed differentially, and three were bermudagrass controls With differences in amount of residual stubble remaining at beginning of autumn. There was only a slight delay in initiation of Tifton 85 spring regrowth relative to the unseeded controls and no apparent stand loss resulting from overseeding cool-season forages. Late spring and summer Tifton 85 production generally was greater on seeded than non-seeded areas, possibly resulting from the nitrogen (N) release from decaying cool-season legumes. Grazing management of winter species in seeded plots and stubble height of bermudagrass in control plots had no effect on bermudagrass performance. Nutritive value responses generally favored overseeded plots. These data, though from one year, show no negative effect on Tifton 85 bermudagrass performance from overseeding and grazing cool-season annual forages during winter.
Keywords: cool season species; nutritive value; Tifton 85; weed